DEVELOPMENT OF A MATHEMATICS MODULE BASED ON A CONTEXTUAL APPROACH TO ENHANCE NUMERACY LITERACY - Rima Fitriyani; Happy Lumbantobing; Jonner Nainggolan (Penelitian dan Pengembangan Ilmu, 2026)
The primary objective of this research is to develop a mathematics module utilizing a contextual approach to enhance the numeracy literacy skills of eighth-grade students at MTs Negeri Kota Jayapura, specifically focusing on relations and functions. Employing the Research and Development (R&D) method with the ADDIE model, the study progressed through analysis, design, development, implementation, and evaluation stages. The findings indicate that the developed module achieved a